2019
DOI: 10.1002/jsfa.9836
|View full text |Cite
|
Sign up to set email alerts
|

Benzenedicarboxylic acid upregulates O48814 and Q9FJQ8 for improved nutritional contents of tomato and low risk of fungal attack

Abstract: BACKGROUND Tomato is an important food item and a cocktail of phytonutrients. In the current study, metabolites from a non‐pathogenic fungal species Penicillium oxalicum have been exploited to obtain nutritionally augmented tomato fruits from the plants to better withstand against Alternaria alternata infection. RESULTS Initially, bioactivity‐guided assay and chromatographic analyses identified the bioactive metabolites of P. oxalicum [benzenedicarboxylic acid (BDA) and benzimidazole]. Then, ≥3 times elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The current research precisely identifies PGK3 as a nutrition controlling protein in V. unguiculata grains, and also discovers its docking with nicotine ligand, for improved functionality. However, the improved activity of the TCA cycle ( Figure 9) could be responsible for disease control, as suggested by Ahmad et al [16].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The current research precisely identifies PGK3 as a nutrition controlling protein in V. unguiculata grains, and also discovers its docking with nicotine ligand, for improved functionality. However, the improved activity of the TCA cycle ( Figure 9) could be responsible for disease control, as suggested by Ahmad et al [16].…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, unveiling the glucanase defenses was included as one of the main tasks of the current study. It has been previously reported that the bioactive compounds alter the physiological parameters and change the nutritional contents in a plant [16]. Using the bioactive compound can pave our way toward nutritionally rich food, which would be helpful in feeding large human populations globally.…”
Section: Introductionmentioning
confidence: 99%
“…Extrolites : Penicillium oxalicum produces oxaline, meleagrin, glandicolin A & B, and roquefortine C ( Nagel et al., 1974 , Nagel et al., 1976 , Steyn and Vleggaar, 1983 , Chen et al., 2015 ), secalonic acids, paecilin C and penicillixanthone ( Steyn, 1970 , Li et al., 2010 , Kim et al., 2012 , Bao et al., 2013 , Wang et al., 2013b , Chen et al., 2015 , Liu et al., 2015 , Chen et al., 2019 ), oxalic acid ( Currie & Thom 1915 ), benzenedicarboxylic acid and benzimidazole ( Ahmad et al. 2019 ), (Z)-3-(3,4-dihydroxyphenyl)-2-foramidoacrylate and decaturins and oxalicins ( Ubillas et al., 1989 , Wang et al., 2013a , Li et al., 2015b , Zhang et al., 2015a ), 2,2’,4,4’-tetrahydroxy-8’-methyl-6-methoxy-acyl-ethyl-diphenylmethanone ( Liu et al., 2015 , Liu et al., 2016a ), hydroxyscytalone ( Ji et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nutrients play an important role in maintaining body functions, especially for patients with severe diseases. Inadequate nutrient intake and impaired utilization can directly induce or aggravate systemic inflammatory responses, exacerbating organ failure (Ahmad et al, 2019). At present, enteral and parenteral nutrition support methods are widely applicated (Nunes & Piuvezam 2019).…”
Section: Discussionmentioning
confidence: 99%